Thermal stability of nanometric TiC-carbon composites: effects of carbon allotropes and Zr milling impurities. Issue 15 (December 2018) - Ramos, J.P.; Stora, T.; Senos, A.M.R.; Bowen, P.
Abstract: In the ISOL (Isotope Separator OnLine) method a target at high temperatures (up to 2300 °C), is bombarded with high energy protons in order to produce isotopes through nuclear reactions which are simultaneously extracted from the target, ionized and delivered to physics experiments. Due to the enhanced isotope release properties of nanosized porous materials, titanium carbide-carbon porous nanocomposites have been developed at CERN and tested up to 1500 °C. In the interest of the ISOL application, in this study we extended the range of temperatures up to 1800 °C, to test the sintering hindering capabilities of different carbon allotropes. Carbon black was the most effective with the smallest TiC crystallite size: <80 nm at 1800 °C. Additionally, using thermodynamic modelling, ex-situ X-ray powder diffraction and in-situ gas phase analysis, we show that there are interesting additional phase and lattice parameter changes due to the ZrO2 impurities from the attrition milling.